Factors affecting climacteric women with SARS-CoV-2 infection: A multinational Latin America study (REDLINC XI). (November 2022) - Vallejo, María S.; Blümel, Juan E.; Bencosme, Ascanio; Calle, Andrés; Dextre, Maribel; Díaz, Karen; López, Marcela; Miranda, Carlos; Ñañez, Mónica; Ojeda, Eliana; Rey, Claudia; Rodrigues, Marcio A.; et al.
Highlights: The association between the climacteric and COVID-19 was evaluated in 1238 women, aged 40–64 years. 24.6 % of the women in the study sample had a positive COVID-19 history. Postmenopausal status was positively associated with a history of COVID-19 and use of menopausal hormone therapy was negatively associated. Housewives and nulliparous women were at lower risk of COVID-19. Smokers, women who have sexual partners, and hypnotic users were at higher risk. Abstract: Objective: To evaluate the association between factors, especially those linked to the climacteric, and a history of COVID-19 infection. Methods: This was an observational, cross-sectional, and analytical study in which women from ten Latin American countries, aged 40–64, who attended a routine health check-up were invited to participate. A positive history for COVID-19 was based on reverse transcription-polymerase chain reaction reports. We evaluated sociodemographic, clinical, lifestyle, anthropometric variables, and menopausal symptoms using the Menopause Rating Scale (MRS). Results: A total of 1238 women were included for analysis, of whom 304 (24.6 %) had a positive history for COVID-19. The median [interquartile range: IQR] age of participants was 53 [IQR 12] years, duration of formal education was 16 [6] years, body mass index 25.6 [5.1] kg/m 2, and total MRS score 10 [13]. In a logistic regression model, factors positively associated with COVID-19 included postmenopausal status and having a family history of dementia (OR: 1.53; 95 % CI: 1.13–2.07, and 2.40; 1.65–3.48, respectively), whereas negatively associated were use of menopausal hormone therapy (current or past), being a housewife, and being nulliparous (OR: 0.47; 95 % CI: 0.30–0.73; 0.72; 0.53–0.97 and 0.56; 0.34–0.92, respectively). Smoking, being sexually active, and use of hypnotics were also factors positively associated with COVID-19. Conclusion: Postmenopausal status and a family history of dementia were more frequent among women who had had COVID-19, and the infection was less frequent among current or past menopause hormone therapy users and in those with less physical contact.